Spirochete Biology: The Post Genomic Era (Current Topics in Microbiology and Immunology,, 2018)
Spirochetes comprise a fascinating group of bacteria. Although diverse in terms of their habitat, ecology and infectivity for vertebrate and non-vertebrate hosts, they are often considered together because of their similar cellular morphologies. This volume brings together an international group of experts to provide essential insights into spirochete biology, with an emphasis on recent advances made possible by the availability of genome sequences. As such, it offers a valuable resource for microbiologists and other scientists with an interest in spirochete biology.